Occupational Health and Safety in Agricultural Production - Yaşar Serhat Saygılı; Bülenr Çakmak (Turkish Journal of Agriculture: Food Science and Technology)
Agricultural production is one of the leading sectors in the world and in our country in terms of employment rates. Agricultural production activities, the importance of which is increasing day by day due to the increasing world population, is an important strategic element for every country. The economy of many countries, including our country, still depends on the products they obtain because of agricultural production. Appropriate agricultural policies should be implemented to increase the productivity in agricultural production, to protect the employed workforce and to ensure its continuity. In addition to establishing appropriate agricultural policies, employed workers should also be protected by laws, regulations and directives. It is a fact that most of the people employed in agricultural production in our country must work under dangerous and harsh conditions without being under legal protection, without union formation and union rights, as in other sectors. Protecting the health of agricultural production workers working under very difficult conditions due to variable climatic conditions, ensuring safe production and ensuring that the necessary Occupational Health and Safety measures are taken should be among the priority items when forming our state’s policies. In this study, the situation in the world and in our country was examined under the title of occupational health and safety in agricultural production. The hazards and risk factors to be encountered in agricultural production have been determined and the Occupational Health and Safety measures to be taken against them have been tried to be explained.